Australian cyclists' engagement in secondary tasks. (March 2020) - Young, Kristie L.; Stephens, Amanda N.; O'Hern, Steve; Koppel, Sjaan
Abstract: Introduction: Distraction is an emerging risk factor for cycling safety. Research from Europe, the United States and Japan indicate that the use of electronic devices is prevalent among cyclists in these countries. However, there is little known about the prevalence of Australian cyclists' engagement in potentially distracting tasks and in non-technology based tasks in particular. This study examined the prevalence of secondary task engagement among Australian cyclists to determine if characteristics, such as age, gender, cycling exposure and personality, predict the frequency of engagement in secondary tasks while riding. Methods: A sample of 646 regular cyclists (defined as cycling at least once per week) completed an online survey assessing the frequency with which they reportedly engage in a range of potentially distracting tasks. Results: Reported engagement in secondary tasks among Australian cyclists was low, particularly for technology-based tasks, with the average reported engagement for many tasks sitting between 'never' and 'hardly ever'. In addition, engagement in secondary tasks while riding was predicted by a number of cyclist characteristics including age, cycling frequency and impulsive/sensation seeking personality traits. Conclusions: Cyclist engagement in any form of distracted cycling may be particularly risky in the Australian context due to a lack of safe cycling infrastructure making the road network less tolerant of distraction-related errors. Findings from this study can inform the design and targeting of policies aimed at reducing distracted cycling in Australia and overseas. Highlights: Examines reported prevalence of secondary task engagement among Australian cyclists. Reported engagement in secondary tasks among Australian cyclists is low. Non-technology based tasks are engaged in more frequently by cyclists than electronic devices. Distracted cycling countermeasures should be targeted at young, frequent cyclists and non-technology tasks.